2021
DOI: 10.48550/arxiv.2108.12422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universality class of Ising critical states with long-range losses

Abstract: We show that spatial resolved dissipation can act on Ising lattices molding the universality class of their critical points. We consider non-local spin losses with a Liouvillian gap closing at small momenta as ∝ q α , with α a positive tunable exponent, directly related to the power-law decay of the spatial profile of losses at long distances. The associated quantum noise spectrum is gapless in the infrared and it yields a class of soft modes asymptotically decoupled from dissipation at small momenta. These mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The most straightforward example of a weak symmetry is when [H, P j,k ] = 0 and Pj,k maps the set of all the Lindblad operators {L µ } into itself, though more exotic cases are possible (e.g. [160][161][162][163][164]). Thus systems satisfying the conditions of Cor.…”
Section: Corollary 2 Fulfilling All the Following Conditions Is Suffi...mentioning
confidence: 99%
“…The most straightforward example of a weak symmetry is when [H, P j,k ] = 0 and Pj,k maps the set of all the Lindblad operators {L µ } into itself, though more exotic cases are possible (e.g. [160][161][162][163][164]). Thus systems satisfying the conditions of Cor.…”
Section: Corollary 2 Fulfilling All the Following Conditions Is Suffi...mentioning
confidence: 99%
“…Recent studies have shown the usefulness of non-local dissipation in generating entanglement between distant qubits in both fields of quantum optics and spintronics, by investigating spins immersed in a optical cavity [67][68][69] and nitrogen-vacancy qubits in proximity to a magnetic medium [70]. For the latter, dynamical phase transitions in the magnet controlled by electrical pumping, may provide an efficient tunability of non-local dissipation, which could be studied along the lines of this work.…”
Section: Superradiance and Lasingmentioning
confidence: 99%
“…Such open quantum systems have attracted many theoretical and experimental researchers in recent years, and nontrivial consequences of dissipation have been uncovered in a variety of quantum phenomena. In particular, universal dynamics has been extensively explored from various viewpoints such as measurement-induced phase transitions [5][6][7][8][9][10][11][12][13][14][15][16], selforganized criticality [17][18][19], and non-equilibrium phase transitions [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Open quantum systems have thus become a novel playground for studying universal quantum non-equilibrium phenomena.…”
Section: Introductionmentioning
confidence: 99%